Indonesia After Joko Widodo: The Increase in Politics and Public Administration (Jurnal Bina Praja, 2017)
This study aims to capture public appraisal, especially student groups as young voters. The public appraisal that will be captured relates to the satisfaction of young voters on the performance of one year of government Jokowi Jusuf Kalla. Using the survey method, this study will be conducted on student groups in the Pancasila and Citizenship Education Study Program, Ahmad Dahlan University. Data collection was done by spreading the questionnaire which then performed tabulation and correlation analysis. This study is expected to be the baseline data in the first year of Jokowi Jusuf Kalla's reign as the basis for future leadership prediction analysis for the next four years. Thus, by knowing the basic pattern in the first year it will be analyzed how would the trend of satisfaction and political beliefs of society until the end of office Joko Widodo.
Keywords: Politics; Economy; Joko Widodo